Detection of Entamoeba histolytica antigen in stool specimens by using ELISA in Basrah province - Al-Yaquob, Aseel (University of Thi-Qar Journal of Science, 2010)
In the present study, we have been used an Enzyme Linked Immunosorbent Assay ( ELISA) for detection of E. histolytica \ E. dispar and comparing it with microscopic examination Sixty five samples were examined by ioden staining was positive in 35 ( 53.6 % ) then these iodine positive samples examined by ELISA a lotof which 33 ( 94.2 % ) were positive in the mean time 4 ( 13.33 % ) were positive in ELISA although that they were negative in microscopic exam.It can be concluded that microscopical examination has low sensitivity and specificity in comparision with ELISA.